1998
DOI: 10.1029/98wr00436
|View full text |Cite
|
Sign up to set email alerts
|

Public perceptions regarding water quality and attitudes toward water conservation in the lower Fraser Basin

Abstract: Abstract. This paper concerns public judgments regarding water quality, public attitudes about water conservation, and related issues in the Lower Fraser Basin of southwest British Columbia, Canada. A written survey was administered to 183 lay subjects in four communities within the Lower Fraser Basin. The results show that subjects generally perceive water quality in specific water bodies as worse than indicated in technical studies of those water bodies. Respondents also indicated a high willingness to engag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 6 publications
(1 reference statement)
0
15
0
Order By: Relevance
“…The potential difference between actual water quality and individual perceptions is perhaps more challenging. McDaniels et al [1998] have documented the possibility of a large divergence between these two. This is of issue for studies such as the current one in that individuals can be expected to base their behavior on personal perceptions, which are unobservable to the analyst, rather than actual conditions, which the analyst hopes to proxy with chemical or subjective measures of quality.…”
Section: Datamentioning
confidence: 99%
“…The potential difference between actual water quality and individual perceptions is perhaps more challenging. McDaniels et al [1998] have documented the possibility of a large divergence between these two. This is of issue for studies such as the current one in that individuals can be expected to base their behavior on personal perceptions, which are unobservable to the analyst, rather than actual conditions, which the analyst hopes to proxy with chemical or subjective measures of quality.…”
Section: Datamentioning
confidence: 99%
“…These techniques also have been used to evaluate public preferences for alternative programs and their characteristics (e.g., Hoehn, Krieger, & Kaplowitz, 1999;Lupi, Kaplowitz, & Hoehn, 2002;McDaniels, Axelrod, & Cavanagh, 1998). For example, Blomquist et al's (2000) budget survey helped measure public preference for statewide and local water quality improvement programs, while other valuation survey techniques were used to measure residents' perceptions and values as they relate to riparian buffers and open space in agricultural watersheds (Qiu & Prato, 1998) as well as suburban watersheds (Qiu, Prato, & Boehrn, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Pendleton et al (2001) reported that residents of Los Angeles County tend to hold perceptions of marine water quality at odds with data on bacteriological measures of water quality collected by local sanitation districts despite education campaigns, and suggested that perception of coastal water quality may be less influenced by coastal education campaigns than by media and other factors. On the other hand, McDaniels et al (1998) reported that residents of a watershed of British Columbia perceived water quality as worse than was indicated by technical reports. The present study showed that social exchange, perception of environmental conditions and personal impressions were often more significant than factual environmental information, as previously reported by Szagun and Pavlov (1995).…”
Section: Implications For Managing Recreational Areasmentioning
confidence: 91%